1989
DOI: 10.1017/s030822960001014x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of volume of food intake on blood flow in the portal vein and the clearance of progesterone from plasma in gilts

Abstract: One hypothesis for the adverse effect which a high food intake in early pregnancy has on early embryo mortality in gilts is that it increases blood flow through the liver and in consequence the rate of removal of progesterone from the blood. To study this aspect the metabolic clearance rate of progesterone (MCR) from plasma and the rate of blood flow in the portal vein were measured concurrently during 14 hour periods in six ovariectomised gilts, weighing 70 to 80 kg, when their food intake was 1 and 3 kg/day.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…However, in our study, estradiol levels were similar in both weaned and lactating does. The origin of lower progesterone levels remains unknown but several hypotheses can be made: 1) the action of estrogen is regulated by a placental luteotrophic hormone (Gadsby and Keyes, 19841, placentas were lighter in the L group than in the W group; consequently, compromised secretion of placental luteotropin may contribute to decreased progesterone concentrations; 2 ) prolactin is required to sustain pregnancy in the rabbit (Hilliard, 19731, whereas high levels of prolactin decreased progesterone production in rabbit (Lin et al, 1987) and therefore progesterone production may be lowered during lactation; 3 ) progesterone production in the rabbit CL is dependent on lipoprotein-delivered cholesterol (Holt, 19891, the mammary gland is a site that uses lipoproteins for milk production (Guesnet and Demarne, 1987) and therefore the supply of lipoproteins to the ovary may not meet the requirements for optimal luteal steroidogenesis in lactating does; and 4 ) the high feed intake that occurs during lactation may alter the metabolic turnover rate of progesterone and influence its peripheral concentration (Symonds and Prime, 1989;Lamb et al, 1991). Whatever the origin, it can be proposed that lower progesterone levels lead to higher fetal mortality.…”
Section: Resultsmentioning
confidence: 99%
“…However, in our study, estradiol levels were similar in both weaned and lactating does. The origin of lower progesterone levels remains unknown but several hypotheses can be made: 1) the action of estrogen is regulated by a placental luteotrophic hormone (Gadsby and Keyes, 19841, placentas were lighter in the L group than in the W group; consequently, compromised secretion of placental luteotropin may contribute to decreased progesterone concentrations; 2 ) prolactin is required to sustain pregnancy in the rabbit (Hilliard, 19731, whereas high levels of prolactin decreased progesterone production in rabbit (Lin et al, 1987) and therefore progesterone production may be lowered during lactation; 3 ) progesterone production in the rabbit CL is dependent on lipoprotein-delivered cholesterol (Holt, 19891, the mammary gland is a site that uses lipoproteins for milk production (Guesnet and Demarne, 1987) and therefore the supply of lipoproteins to the ovary may not meet the requirements for optimal luteal steroidogenesis in lactating does; and 4 ) the high feed intake that occurs during lactation may alter the metabolic turnover rate of progesterone and influence its peripheral concentration (Symonds and Prime, 1989;Lamb et al, 1991). Whatever the origin, it can be proposed that lower progesterone levels lead to higher fetal mortality.…”
Section: Resultsmentioning
confidence: 99%
“…The demonstration by Parr et al (1987) in ewes and Ashworth (1990) in gilts that the 25-30 % reduction in embryo survival arising from high-plane feeding could be avoided by the administration of exogenous progesterone, one of the key hormones in the maintenance of pregnancy, provides an insight into the mechanisms involved. It would appear that high food intakes, via their stimulatory effects on both hepatic blood flow and the metabolic clearance rate of progesterone (Symonds & Prime, 1989), cause a decrease in plasma progesterone to levels that may compromise embryo growth and survival ; certainly there is ample evidence of lower circulating concentrations on high as opposed to low food intakes in early pregnancy (McKelvey & Robinson, 1986;Parr et al 1987, sheep;Prime et at. 1988, pig).…”
Section: F E R T I L I Z a T I O N A N D E M B R Y O S U R V I V A Lmentioning
confidence: 99%
“…However, a higher plane of nutrition has been reported to reduce embryo survival rate in ewes (Parr et al 1987). Higher protein or energy intakes have a stimulatory effect on hepatic blood flow which influences the metabolic clearance rate of progesterone (Symonds & Prime, 1989) causing its decrease to an extent that may compromise embryo survival and growth (McKelvey & Robinson, 1986). In this context, Parr et al (1987) demonstrated that the reduction in the rate of embryo survival arising as a result of a higher plane of protein and energy nutrition can be avoided by administration of exogenous progesterone.…”
Section: E M B R Y O Survivalmentioning
confidence: 99%